Laying the Foundation for a Robust Health Care System in Kenya : Kenya Public Expenditure Review - World Bank Group (Washington, DC, 2015)
Kenya is currently in an expansionary phase of its fiscal policy reflected in a widening primary deficit. The fiscal framework is marked by a significant fiscal expansion over the last three years, 2011/12 to 2013/14. The fiscal stimulus implemented in 2009/10 increased aggregate spending by 2 percent of Gross Domestic Product (GDP). However the envisaged fiscal retrenchment at the end of the program did not materialize and fiscal expansion continued with the general election in 2013. Aggregate expenditure averaged 25 percent and revenue at 18 percent of GDP. The fiscal deficit financed through debt is reflected in the doubling of the primary deficit (commitment basis) now in the range of 3.3 percent of GDP, and the rising stock of public debt from 37 percent to 43 percent of GDP (net of deposits), of which about half 22 percent was external debt in 2013/14. The fiscal developments have seen an increase in the share of debt service in total spending from 13 percent to 15 percent of recurrent spending, equivalent to 2.6 percent of GDP. Kenya s debt service is higher among East Africa Community (EAC) peers, 2 percentage points above Ethiopia and Rwanda, and 1 percentage point higher than Uganda and Tanzania.